2022
DOI: 10.1186/s12985-022-01865-4
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoproteins may play a crucial role in COVID-19

Abstract: Background Lipids play a central role in the virus life cycle and are a crucial target to develop antiviral therapeutics. Importantly, among the other lipoproteins, the ‘good cholesterol’ high-density lipoprotein (HDL) has been widely studied for its role in not only cardiovascular but several infectious diseases as well. Studies have suggested a role of serum lipids and lipoproteins including HDL, total cholesterol (TC), triglycerides (TG), and low-density lipoproteins (LDL) in several viral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…The observed association between low HDL levels and an augmented inflammatory response in HD patients with long COVID underscores the intricate interplay between dyslipidemia, chronic inflammation, and the lingering effects of SARS-CoV-2 infection. The significant decrease in HDL levels observed in HD patients with long COVID is consistent with prior research in the general population, emphasizing the influence of COVID-19 on lipid metabolism [8][9][10]. Similar results were reported in the HD population evaluating the impact of pre-existing HDL levels and immediate COVID-19 outcomes [11].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The observed association between low HDL levels and an augmented inflammatory response in HD patients with long COVID underscores the intricate interplay between dyslipidemia, chronic inflammation, and the lingering effects of SARS-CoV-2 infection. The significant decrease in HDL levels observed in HD patients with long COVID is consistent with prior research in the general population, emphasizing the influence of COVID-19 on lipid metabolism [8][9][10]. Similar results were reported in the HD population evaluating the impact of pre-existing HDL levels and immediate COVID-19 outcomes [11].…”
Section: Discussionsupporting
confidence: 88%
“…Emerging evidence implicates dyslipidemia, particularly low levels of high-density lipoprotein (HDL), is linked to heightened susceptibility to COVID-19, increased cardiovascular risks, elevated infection severity, and higher mortality rates in the general population [8][9][10]. In addition, our previous report has shown that low HDL levels before the onset of infection are independently associated with COVID-19 morbidity, severity and mortality in patients undergoing HD [11].…”
Section: Introduction / вступmentioning
confidence: 98%
“…In the controls (10 COVID-19 negative controls), 100% of samples had moderately low HDL but none severely low HDL levels. 48 More studies are needed to establish the cause…”
Section: Covid 19mentioning
confidence: 99%
“…Several studies have investigated the relationship between HDL cholesterol levels and COVID-19 outcomes [22][23][24][25][26][27]. Specifically, low levels of plasma HDL cholesterol and alterations in HDL composition have been associated with increased disease severity and worse clinical outcomes in COVID-19 patients [28,29].…”
Section: Introductionmentioning
confidence: 99%